Notes to a Political Anthropology of Time - Zuker, Fábio (Cadernos de Campo (São Paulo, 1991), 2017)
This article develops between the fields of contemporary anthropology, historiography and political thought. From the critical referential of symmetrical anthropology – its points of contact and detachment from a particular postcolonial thought – we point to the way modernity claims a specificunderstanding of the category of time through historical discourse. We interpretthe role that this category plays in the image of modernity itself and its contemporary form, and the political consequences of such conceptions. Finally, we present a certain recent anthropological production, concerned with analyzing the relationship between time and politics involved in processes of resistance of “non-modern” peoples to the expansion of modernity in its present form. The final point of the article is thus to punctuate, in this proposal of symmetrical or reverse anthropology, which other questions these modes of existence place on the meanings attributed to the passing of time in modern cosmology itself.